Accounting process-related CO2 emissions from global cement production under Shared Socioeconomic Pathways. (20th May 2018) - Zhang, Cheng-Yao; Han, Rong; Yu, Biying; Wei, Yi-Ming
Abstract: Cement production is the main source of industrial process-related CO2 emissions, taking up approximately half of total industrial process-related CO2 emissions. However, limited research has investigated the process-related CO2 emissions from global cement production, in particular, has not taken into account the impacts of dynamic socio-economic development context. This study aims to explore the trajectory of industrial process-related CO2 emissions in the cement industry under different Shared Socioeconomic Pathways (SSPs), to provide more evidence for the existing climate change integrated assessment analysis. By investigating the relationship between per capita GDP and per capita cement production process-related CO2 emissions drawing on the historical data during 1950–2014 in 31 developed countries, the cement production process-related CO2 emissions from 175 countries in 12 regions in the world during 2015–2100 under five SSP scenarios are given here. The results show that the largest amount of global cumulative cement process-related CO2 emissions would be 45.45 billion tons under SSP3 scenario. The countries that contribute the most to the global cumulative cement production process-related CO2 emissions from 2015 to 2100 are India, China, Nigeria, United States of America and Pakistan. Highlights: The industrial process-related CO2 emissions from cement production is targeted. Project global process-related CO2 emissions under five Shared Socioeconomic Pathways. Cement process-related CO2 emissions from 175 countries in 2015–2100 are given. The global cumulative process-related CO2 emissions under SSP3 are the highest. The process-related CO2 emissions are quite different in 12 regions under SSP1-SSP5.